The Relationship between Agents and Structures in Changing the Authority of Halal Certificates in Indonesia - Azhari, Munir; Ulinnuha, Roma (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The existence of Law No. 33 of 2014, which contains changes in the authority of halal certificates Âfrom the Indonesian Ulama Council (MUI) to the Halal Product Guarantee Agency (BPJPH), has created a polemic in society. Halal certificate, which was previously voluntary, has now become mandatory. This change in authority raises polemics. The civil society and business actors as agents and the JPH Law as a structure are the basis for the relationship between agents and structures in reconciling this polemic. Giddens' theory, which conceptualizes the duality between agents and structures, can be a useful analysis to reconcile these issues. This study aims to analyze the relationship between agents and structures in the change of authority and explain the duality between agents and structures from the perspective of structuration theory. This type of research is qualitative by using an interpretative approach to the core object of the problem in the study. The result of this study is the existence of a relationship between agents and structures to walk together in implementing halal certification. The agents who play a role in changing halal authority, consisting of BPJPH, business actors, and the general public in the structure (JPH Law), are expected synergize. It is intended to generate civil society who understands the dynamics of agent and structural changes in changing the authority of this halal certification.